Front-line Treatment for Chronic Lymphocytic Leukemia in 2025: Finite Duration Versus Continuous Treatment (Canadian Hematology Today, 2025)
Chronic lymphocytic leukemia (CLL) is an indolent lymphoproliferative disorder and is the most common hematologic malignancy in Western populations. In Canada, an estimated 2,000 or more new cases are diagnosed each year. Improvements in diagnostic techniques, enhanced prognostication methods, and the development of targeted treatments have revolutionized the management of CLL over the past decade. Despite an ever-expanding therapeutic landscape (Figure 1), the decision to initiate treatment continues to be guided by the International Workshop on CLL criteria.For patients who require treatment, we now have a choice of two treatment approaches based on current Health Canada approvals: fixed‑duration therapy (e.g., chemoimmunotherapy, venetoclax‑obinutuzumab [VO], or ibrutinib‑venetoclax [IV]) versus continuous treatment until disease progression or toxicity (i.e., Bruton’s tyrosine kinase inhibitors [BTKi]). In this review, we will summarize the evidence for these two approaches and provide our views on factors that may influence treatment selection.